x2-2x+6=5x

Simple and best practice solution for x2-2x+6=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2-2x+6=5x equation:



x2-2x+6=5x
We move all terms to the left:
x2-2x+6-(5x)=0
We add all the numbers together, and all the variables
x^2-7x+6=0
a = 1; b = -7; c = +6;
Δ = b2-4ac
Δ = -72-4·1·6
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-5}{2*1}=\frac{2}{2} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+5}{2*1}=\frac{12}{2} =6 $

See similar equations:

| 5x+7x-21=63-9x | | 11=3-12y | | -7(-9x-22=(-665 | | -8+8=-3x+3 | | 3.5y=2.3y+7.2 | | x+2=-10+2x | | -5(x+2)2;x=-3 | | 3u+8=26 | | 3(8+6m)=-102 | | g-0.003=-0.0017 | | 0=-401,6+39,2x+4.9x^2 | | 1y+6+4y-13=26 | | 3.5z-2.7z= | | x=(2x-9)- | | h+50.3=80.2 | | 5=m+12.5-m | | 2v+16=36 | | 7u+-10=-73 | | 6p-8=-5p+18 | | -5+w/2=-1 | | 4(1+3)=3a(2a+1) | | 32​ y−7​ =9 | | 56+e=450 | | 17p-8=18 | | (3+x)2=4 | | w^2+15w-225=0 | | 1,105=(x+25)13 | | 1/3x+3=26+16/8x-23 | | 15z-6=11z-50 | | 26=17p | | 12m+20=175 | | l-0.02=-0.006 |

Equations solver categories